Assessment of Gingival Biotype and Keratinized Gingival Width of Maxillary Anterior Region in Individuals with Different Types of Malocclusion - Alkan, Özer (Turk J Orthod, 2018)
OBJECTIVE: The aim of the present study is to evaluate the relationship of gingival thickness and width of keratinized gingiva with different malocclusion groups and amount of crowding. METHODS: A total of 181 periodontally healthy subjects were enrolled in the present study. The study participants were divided into three malocclusion groups: Angle Class I, Angle Class II, and Angle Class III. Each group was divided into subgroups according to the amount of dental crowding, namely mild, moderate, and severe. The width of keratinized gingiva was calculated as the distance between mucogingival junction and free gingival margin, whereas gingival thickness was determined by a transgingival probing technique. RESULTS: Tooth numbers 13 and 23 were observed to have thin gingival biotype. The width of keratinized gingiva for tooth numbers 13 and 23 was narrower in the severe crowding group than in the moderate and mild crowding groups. The relationship of gingival thickness and width of keratinized gingiva with Angle classification was not found to be significant. CONCLUSION: Although it is thought that there is a relationship between gingival thickness, width of keratinized gingiva, and Angle classification with regard to malaligned teeth, this cross-sectional evaluation of 181 patients failed to show a significant relationship.